SpringerOpen Newsletter

Receive periodic news and updates relating to SpringerOpen.

Open Access Research

Existence of nontrivial solutions to perturbed p-Laplacian system in ℝ N involving critical nonlinearity

Huixing Zhang* and Wenbin Liu

Author affiliations

Department of Mathematics, China University of Mining and Technology, Xuzhou, Jiangsu 221116, People's Republic of China

For all author emails, please log on.

Citation and License

Boundary Value Problems 2012, 2012:53  doi:10.1186/1687-2770-2012-53

The electronic version of this article is the complete one and can be found online at: http://www.boundaryvalueproblems.com/content/2012/1/53


Received:29 September 2011
Accepted:4 May 2012
Published:4 May 2012

© 2012 Zhang and Liu; licensee Springer.

This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Abstract

We consider a p-Laplacian system with critical nonlinearity in ℝN. Under the proper assumptions, we obtain the existence of nontrivial solutions to perturbed p-Laplacian system by using the variational approach.

MR Subject Classification: 35B33; 35J60; 35J65.

Keywords:
p-Laplacian system; critical nonlinearity; variational methods.

1 Introduction

This article is concerned with the existence of solutions to the following nonlinear perturbed p-Laplacian system

{ ε p Δ p u + V ( x ) | u | p 2 u = K ( x ) | u | p * 2 u + H u ( u , v ) , x N , ε p Δ p v + V ( x ) | v | p 2 v = K ( x ) | v | p * 2 v + H v ( u , v ) , x N , u ( x ) , v ( x ) > 0 , u ( x ) , v ( x ) 0 as | x | , (1.1)

where Δpu = div(|∇u|p-2u) is the p-Laplacian operator, 1 < p < N and p* = Np/(N − p) is the critical exponent.

Throughout the article, we will assume that:

(V0) V C(ℝN), V (0) = inf V (x) = 0 and there exists b > 0 such that the set νb := {x ∈ ℝN : V (x) < b} has finite Lebesgue measure;

(K0) K(x) ∈ C(ℝN), 0 < inf K ≤ sup K < ∞;

(H1) H C1(ℝ2) and Hs, Ht = o(|s|p-1 + |t|p-1) as |s| + |t| → 0;

(H2) there exist c > 0 and p < q < p* such that

| H s ( s , t ) | , | H t ( s , t ) | c ( 1 + | s | q - 1 + | t | q - 1 ) ;

(H3) There are a0 > 0, θ ∈ (p, p*) and α, β > p such that H(s, t) ≥ a0(|s|α + |t|β) and 0 < θH(s, t) ≤ sHs + tHt.

Under the above mentioned conditions, we will get the following result.

Theorem 1. If (V0), (K0) and (H1)-(H3) hold, then for any σ > 0, there is εσ > 0 such that if ε < εσ, the problem (1.1) has at least one positive solution (uε, vε) which satisfy

θ - p p θ N ( ε p | u ε | p + ε p | v ε | p + V ( x ) | u ε | p + V ( x ) | v ε | p ) σ ε N .

The scalar form of the problem (1.1) is as follows

- ε p Δ p u + V ( x ) | u | p - 2 u = K ( x ) | u | p * - 2 u + h ( x , u ) , x N . (1.2)

The Equation (1.2) has been studied in many articles. The case p = 2 was investigated extensively under various hypotheses on the potential and the nonlinearity by many authors including Brézis and Nirenberg [1], Ambrosetti [2] and Guedda and Veron [3] (see also their references) in bounded domains. As far as unbounded domains are concerned, we recall the work by Benci and Cerami [4], Floer and Weistein [5], Oh [6], Clapp [7], Del Pino and Felmer [8], Cingolani and Lazzo [9], Ding and Lin [10]. Especially, in [10], the authors studied the Equation (1.2) in the case p = 2. In that article, they made the following assumptions:

(A1) V C(ℝN), min V = 0 and there is b > 0 such that the set νb := {x ∈ ℝN : V (x) < b} has finite Lebesgue measure;

(A2) K(x) ∈ C(ℝN), 0 < inf K ≤ sup K <

(B1) h C(ℝN × ℝ) and h(x, u) = o(|u|) uniformly in x as |u| → 0;

(B2) there are c0 > 0, q < 2* such that |h(x, u)| ≤ c0(1 + |u|q-1) for all (x, u);

(B3) there are a0 > 0, p > 2 and µ > 2 such that H(x, u) = a0|u|p and µH(x, u) ≤ h(x, u)u for all (x, u), where H ( x , u ) = 0 u h ( x , s ) d s .

That article obtained the existence of at least one positive solution uε of least energy if the assumptions (A1)-(A2) and (B1)- (B3) hold.

For the Equation (1.2) in the case p ≠ 2, we recall some works. Garcia Azorero and Peral Alonso [11] considered (1.2) with ε ≤ 1, V (x) = µ, K(x) = 1, h(x, u) = 0 and proved that (1.2) has a solution if p2 N and µ ∈ (0, λ1), where λ1 is the first eigenvalue of the p-Laplacian. In [12], Alves and Ding studied the same problem of [11] and obtained the multiplicity of positive solutions in bounded domain Ω ⊂ ℝN. Moreover, Liu and Zheng [13] investigated (1.2) in ℝN with ε = 1 and K(x) = 0. Under the sign-changing potential and subcritical p-superlinear nonlinearity, the authors got the existence result.

Motivated by some results found in [10,11,13], a natural question arises whether existence of nontrivial solutions continues to hold for the p-Laplacian system with the critical nonlinearity in ℝN.

The main difficulty in the case above mentioned is the lack of compactness of the energy functional associated to the system (1.1) because of unbounded domain ℝN and critical nonlinearity. To overcome this difficulty, we make careful estimates and prove that there is a Palais-Smale sequence that has a strongly convergent sequence. The method or idea here is similar to the one of [10]. We can prove that the functional associated to (1.1) possesses (PS)c condition at some energy level c. Furthermore, we prove the existence result by using the mountain pass theorem due to Rabinowitz [14].

The main result in the present article concentrates on the existence of positive solutions to the system (1.1) and can be seen as a complement of the results developed in [10,11,13].

This article is organized as follows. In Section 2, we give the necessary notations and preliminaries. Section 3 is devoted to the behavior of (PS)c sequence and the mountain geometry structure. Finally, in Section 4, we prove the existence of nontrivial solution.

2 Notations and preliminaries

Let C 0 ( N ) denote the collection of smooth functions with compact support and D1,p(ℝN) be the completion of C 0 ( N ) under

| | u | | p = N | u | p d x .

We introduce the space

E ( N , V ) = { u W 1 , p ( N ) : N V ( x ) | u | p < }

equipped with the norm

| | u | | E = N ( | u | p + V ( x ) | u | p ) 1 p

and the space

E λ ( N , V ) = u W 1 , p ( N ) : N λ V ( x ) | u | p < , λ > 0

under

| | u | | λ = ( N | u | p + λ V ( x ) | u | p ) ) 1 p .

Observe that ‖ · ‖E is equivalent to the one ‖ · ‖λ for each λ > 0. It follows from (V0) that E(ℝN, V) continuously embeds in W1,p(ℝN).

Set B = Eλ × Eλ and | | ( u , v ) | | λ = | | u | | λ p + | | v | | λ p for any (u, v) ∈ B. Let λ = ε-p in the system (1.1), then (1.1) is changed into

{ Δ p u + λ V ( x ) | u | p 2 u = λ K ( x ) | u | p * 2 u + λ H u ( u , v ) , N , Δ p v + λ V ( x ) | v | p 2 v = λ K ( x ) | v | p * 2 v + λ H v ( u , v ) , x N , u ( x ) , v ( x ) > 0 , u ( x ) , v ( x ) 0 , as | x | . (2.1)

In order to prove Theorem 1, we only need to prove the following result.

Theorem 2. Let (V0), (K0) and (H1)-(H3) be satisfied. Then for any σ > 0, there exists Λσ > 0 such that if λ ≥ Λσ , the system (2.1) has at least one least energy solution (uλ, vλ) satisfying

θ - p p θ N ( | u λ | p + | v λ | p + λ V ( x ) ( | u λ | p + | v λ | p ) ) σ λ 1 - N p . (2.2)

The energy functional associated with (2.1) is defined by

I λ ( u , v ) = 1 p N ( | u | p + λ V ( x ) | u | p + | v | p + λ V ( x ) | v | p ) - λ p * N K ( x ) ( | u | p * + | v | p * ) - λ N H ( u , v ) = 1 p | | ( u , v ) | | λ p - λ N G ( u , v ) ,

where G ( u , v ) = 1 p * K ( x ) ( | u | p * + | v | p * ) + H ( u , v ) .

From the assumptions of Theorem 2, standard arguments [14] show that Iλ C1(B, ℝ) and its critical points are the weak solutions of (2.1).

3 Technical lemmas

In this section, we will recall and prove some lemmas which are crucial in the proof of the main result.

Lemma 3.1. Let the assumptions of Theorem 2 be satisfied. If the sequence {(un, vn)} ⊂ B is a (PS)c sequence for Iλ, then we get that c ≥ 0 and {(un, vn)} is bounded in the space B.

Proof. One has

I λ ( u n , v n ) - 1 θ I λ ' ( u n , v n ) ( u n , v n ) = 1 p | | ( u n , v n ) | | λ p - λ p * N K ( x ) ( | u n | p * + | v n | p * ) - λ N H ( u n , v n ) - 1 θ | | ( u n , v n ) | | λ p - λ N K ( x ) ( | u n | p * + | v n | p * ) - λ N ( u n H s ( u n , v n ) + v n H t ( u n , v n ) ) = 1 p - 1 θ | | ( u n , v n ) | | λ p + 1 θ - 1 p * λ N K ( x ) ( | u n | p * + | v n | p * ) + λ N 1 θ ( u n H s ( u n , v n ) + v n H t ( u n , v n ) ) - H ( u n , v n )

By the assumptions (K0) and (H3), we have

I λ ( u n , v n ) - 1 θ I λ ( u n , v n ) ( u n , v n ) 1 p - 1 θ | | ( u n , v n ) | | λ p .

Together with Iλ(un, vn) → c and I λ ( u n , v n ) 0 as n → ∞, we easily obtain that the (PS)c sequence is bounded in B and the energy level c ≥ 0. □

From Lemma 3.1, there exists (u, v) ∈ B such that (un, vn) ⇀ (u, v) in B. Furthermore, passing to a subsequence, we have un u and vn v in L l o c d ( N ) for any d ∈ [p, p*) and un u, vn v a.e. in ℝN.

Lemma 3.2. Let d ∈ [p, p*). There exists a subsequence { ( u n j , v n j ) } such that for any ε > 0, there is rε > 0 with

lim i sup B i \ B r ( | u n i | d + | v n i | d ) ε

for any r ≥ rε , where Br := {x ∈ ℝN : |x| ≤ r}.

Proof. The proof of Lemma 3.2 is similar to the one of Lemma 3.2 of [10], so we omit it. □

Let η C(ℝ+) be a smooth function satisfying 0 ≤ η(t) 1, η(t) = 1 if t ≤ 1 and η(t) = 0 if t ≥ 2. Define ũ j ( x ) = η ( 2 | x | / j ) u ( x ) , j ( x ) = η ( 2 | x | / j ) v ( x ) . It is obvious that

| | u - ũ j | | λ 0 and | | v - j | | λ 0 as  j . (3.1)

Lemma 3.3. One has

lim j N ( H s ( u n j , v n j ) - H s ( u n j - ũ j , v n j - j ) - H s ( ũ j , j ) ) φ = 0

and

lim j N ( H t ( u n j , v n j ) - H t ( u n j - ũ j , v n j - v j ) - H t ( ũ j , j ) ) ψ = 0

uniformly in (φ, ψ) ∈ B with ‖(φ, ψB ≤ 1.

Proof. From the assumptions (H1)-(H2) and Lemma 3.2, we have

lim j sup N ( H s ( u n j , v n j ) H s ( u n j u ˜ j , v n j v ˜ j ) H s ( u ˜ j , v ˜ j ) ) φ = lim j sup B j ( H s ( u n j , v n j ) H s ( u n j u ˜ j , v n j v ˜ j ) H s ( u ˜ j , v ˜ j ) ) φ = lim j sup B j \ B r ( H s ( u n j , v n j ) H s ( u n j u ˜ j , v n j v ˜ j ) H s ( u ˜ j , v ˜ j ) ) φ c lim j sup B j \ B r ( | u n j | p 1 + | v n j | p 1 + | u n j | q 1 + | v n j | q 1 + | u ˜ j | p 1 + | v ˜ j | p 1 + | u ˜ j | q 1 + | v ˜ j | q 1 + | u n j u ˜ j | p 1 + | v n j v ˜ j | p 1 + | u n j u ˜ j | q 1 + | v n j v ˜ j | q 1 ) φ c 1 lim j sup B j \ B r ( | u n j | p 1 + | v n j | p 1 + | u ˜ j | p 1 + | v ˜ j | p 1 ) φ + c 2 lim j sup B j \ B r ( | u n j | q 1 + | v n j | q 1 + | u ˜ j | q 1 + | v ˜ j | q 1 ) φ (3.2)

By Hölder inequality and Lemma 3.2, it follows that

lim j sup B j \ B r | u n j | p - 1 | φ | lim j sup B j \ B r | u n j | p p - 1 p B j \ B r | φ | p 1 p lim j sup B j \ B r | u n j | p p - 1 p N | φ | p 1 p lim j sup B j \ B r | u n j | p p - 1 p = 0

and

lim j sup B j \ B r | u n j | p - 1 | φ | lim j sup B j \ B r | u n j | p q - 1 p B j \ B r | φ | q 1 q lim j sup B j \ B r | u n j | q q - 1 q N | φ | q 1 q lim j sup B j \ B r | u n j | q q - 1 q = 0

Similarly, we get

lim j sup B j \ B r ( | v n j | p - 1 | + | ũ j | p - 1 + | j | p - 1 ) φ = 0

and

lim j sup B j \ B r ( | v n j | q - 1 | + | ũ j | q - 1 + | j | q - 1 ) φ = 0 .

Thus

lim j N ( H s ( u n j , v n j ) - H s ( u n j - ũ j , v n j - j ) - H s ( ũ j , j ) ) φ = 0 .

From the similar argument, we also get

lim j N ( H t ( u n j , v n j ) - H t ( u n j - ũ j , v n j - j ) - H t ( ũ j , j ) ) ψ = 0 .

Lemma 3.4. One has along a subsequence

I λ ( u n - ũ n , v n - n ) c - I λ ( u , v )

and

I λ ( u n - ũ n , v n - n ) 0 in  B - 1 ( the dual space of  B ) .

Proof. From the Lemma 2.1 of [15] and the argument of [16], we have

I λ ( u n - ũ n , v n - n ) = 1 p N ( | u n - ũ n | p + λ V ( x ) | u n - ũ n | p + | v n - n | p + λ V ( x ) | v n - n | p ) - λ p * N K ( x ) ( | u n - ũ n | p * + | v n - n | p * ) - λ N H ( u n - ũ n , v n - n ) = I λ ( u n , v n ) - I λ ( ũ n , n ) + λ p * N K ( x ) ( ( | u n | p * - | u n - ũ n | p * - | ũ n | p * ) + ( | v n | p * - | v n - n | p * - | n | p * ) ) + λ N ( H ( u n , v n ) - H ( u n - ũ n , v n - n ) - H ( ũ n , n ) ) + o ( 1 ) .

By (3.1) and the similar idea of proving the Brézis-Lieb Lemma [17], it is easy to get

lim n N K ( x ) ( ( | u n | p * - | u n - ũ n | p * - | ũ n | p * ) + ( | v n | p * - | v n - n | p * - | n | p * ) ) = 0

and

lim n N ( H ( u n , v n ) - H ( u n - ũ n , v n n ) - H ( ũ n , n ) ) = 0 .

In connection with the fact Iλ (un, vn) → c and I λ ( ũ n , n ) I λ ( u , v ) , we obtain

I λ ( u n - ũ n , v n - n ) c - I λ ( u , v ) .

In the following, we will verify the fact I λ ( u n - ũ n , v n - n ) 0 .

For any (φ, ψ) ∈ B, it follows that

I λ ' ( u n u ˜ n , v n v ˜ n ) ( φ , ψ ) = I λ ' ( u n , v n ) ( φ , ψ ) I λ ' ( u ˜ n , v ˜ n ) ( φ , ψ ) + λ N K ( x ) [ ( | u n | p * 2 u n | u n u ˜ n | p * 2 ( u n u ˜ n ) | u ˜ n | p * 2 u ˜ n ) φ + ( | v n | p * 2 v n | v n v ˜ n | p * 2 ( v n v ˜ n ) | v ˜ n | p * 2 v ˜ n ) ψ ] + λ N [ ( H s ( u n , v n ) H s ( u n u ˜ n , v n v ˜ n ) H s ( u ˜ n , v ˜ n ) ) φ + ( H t ( u n , v n ) H t ( u n u ˜ n , v n v ˜ n ) H t ( u ˜ n , v ˜ n ) ) ψ ] + o ( 1 ) .

Standard argument shows that

lim n N K ( x ) ( | u n | p * - 2 u n - | u n - ũ n | p * - 2 ( u n - ũ n ) - | ũ n | p * - 2 ũ n ) φ = 0

and

lim n N K ( x ) ( | v n | p * - 2 v n - | v n - n | p * - 2 ( v n - n ) - | n | p * - 2 n ) ψ = 0

uniformly in ‖φ, ψ)‖B 1.

By Lemma 3.3, we have

lim n N ( H s ( u n , v n ) - H s ( u n - ũ n , v n - n ) - H s ( ũ n , n ) ) φ = 0

and

lim n N ( H t ( u n , v n ) - H t ( u n - ũ n , v n - n ) - H t ( ũ n , n ) ) ψ = 0

uniformly in ‖(φ, ψ)‖B 1. From the facts above mentioned, we obtain

I λ ( u n - ũ n , v n - n ) 0 in  B - 1 .

Let u n 1 = u n - ũ n , v n 1 = v n - n , then u n - u = u n 1 + ( ũ n - u ) , v n - v = v n 1 + ( n - v ) . From (3.1), we get (un, vn) → (u, v) in B if and only if ( u n 1 , v n 1 ) ( 0 , 0 ) in B.

Observe that

I λ ( u n 1 , v n 1 ) - 1 p I λ ' ( u n 1 , v n 1 ) ( u n 1 , v n 1 ) = 1 p - 1 p * λ N K ( x ) ( | u n 1 | p * + | v n 1 | p * ) + λ N 1 p ( u n 1 H s ( u n 1 , v n 1 ) + v n 1 H t ( u n 1 , v n 1 ) ) - H ( u n 1 , v n 1 ) λ N N K ( x ) ( | u n 1 | p * + | v n 1 | p * ) λ N K min N ( | u n 1 | p * + | v n 1 | p * ) ,

where K min = inf x N K ( x ) > 0 .

Thus by Lemma 3.4, we get

| | ( u n 1 , v n 1 ) | | p * p * N ( c - I λ ( u , v ) ) λ K min + o ( 1 ) . (3.3)

Now, we consider the energy level of the functional Iλ below which the (PS)c condition hold.

Let Vb(x):= max{V (x), b}, where b is the positive constant in the assumption (V0). Since the set νb has finite measure and u n 1 , v n 1 0 in L loc p ( N ) , we get

N V ( x ) ( | u n 1 | p + | v n 1 | p ) = N V b ( x ) ( | u n 1 | p + | v n 1 | p ) + o ( 1 ) . (3.4)

From (K0), (H1)-(H3) and Young inequality, there is Cb > 0 such that

N ( K ( x ) ( | u | p * + | v | p * ) + u H s ( u , v ) + v H t ( u , v ) ) b ( | | u | | p p + | | v | | p p ) + C b ( | | u | | p * p * + | | v | | p * p * ) . (3.5)

Let S be the best Sobolev constant of the immersion

S | | u | | p * p N | u | p for all  u W 1 , p ( N ) .

Lemma 3.5. Let the assumptions of Theorem 2 be satisfied. There exists α0 > 0 independent of λ such that, for any (PS)c sequence {(un, vn)} ⊂ B for Iλ with (un, vn) ⇀ (u, v), either (un, vn) (u, v) or c - I λ ( u , v ) α 0 λ 1 - N p .

Proof. Assume that (un, vn) ↛ (u, v), then

lim inf n | | ( u n 1 , v n 1 ) | | λ > 0

and

c - J λ ( u , v ) > 0 .

By the Sobolev inequality, (3.4) and (3.5), we get

S ( | | u n 1 | | p * p + | | v n 1 | | p * p ) N ( | u n 1 | p + | v n 1 | p ) = N ( | u n 1 | p + λ V ( x ) | u n 1 | p + | v n 1 | p + λ V ( x ) | v n 1 | p ) - λ N V ( x ) ( | u n 1 | p + | v n 1 | p ) = λ N K ( x ) ( | u n 1 | p * + | v n 1 | p * ) + u n 1 H s ( u n 1 , v n 1 ) + v n 1 H t ( u n 1 , v n 1 ) - λ N V ( x ) ( | u n 1 | p + | v n 1 | p ) + o ( 1 ) λ b ( | | u n 1 | | p p + | | v n 1 | | p p ) + λ C b ( | | u n 1 | | p * p * + | | v n 1 | | p * p * ) - λ b ( | | u n 1 | | p p + | | v n 1 | | p p ) + o ( 1 ) = λ C b ( | | u n 1 | | p * p * + | | v n 1 | | p * p * ) + o ( 1 ) .

This, together with lim inf n ( | | u n 1 | | p * p * + | | v n 1 | | p * p * ) > 0 and (3.3), gives

S λ C b ( | | u n 1 | | p * p * + | | v n 1 | | p * p * ) p * - p p * + o ( 1 ) λ C b N ( c - I λ ( u , v ) ) λ K min p N + o ( 1 ) = λ 1 - p N C b N K min p N ( c - I λ ( u , v ) ) p N + o ( 1 ) .

Set α 0 = S N p C b - N p N - 1 K min , then

α 0 λ 1 - N p c - I λ ( u , v ) + o ( 1 ) .

This proof is completed. □

Since W 1 , p ( N ) L p * ( N ) is not compact, Iλ does not satisfy the (PS)c condition for all c > 0. But Lemma 3.5 shows that Iλ satisfies the following local (PS)c condition.

Lemma 3.6. From the assumptions of Theorem 2, there exists a constant α0 > 0 independent of λ such that, if a (PS)c sequence {(un, vn)} ⊂ B for Iλ satisfies c α 0 λ 1 - N p , the sequence {(un, vn)} has a strongly convergent subsequence in B.

Proof. By the fact c α 0 λ 1 - N p , we have

c - I λ ( u , v ) α 0 λ 1 - N p - I λ ( u , v ) .

This, together with Iλ(u, v) ≥ 0 and Lemma 3.5, gives the desired conclusion. □

Next, we consider λ = 1. From the following standard argument, we get that Iλ possesses the mountain-pass structure.

Lemma 3.7. Under the assumptions of Theorem 2, there exist αλ, ρλ > 0 such that

I λ ( u , v ) > 0 if 0 < | | ( u , v ) | | λ < ρ λ and  I λ ( u , v ) α λ if | | ( u , v ) | | λ = ρ λ .

Proof. By (3.5), we get that for any δ > 0, there is Cδ > 0 such that

N G ( u , v ) δ ( | | u | | p p + | | v | | p p ) + C δ ( | | u | | p * p * + | | v | | p * p * ) .

Thus

I λ ( u , v ) = 1 p | | ( u , v ) | | λ p - λ N G ( u , v ) 1 p | | ( u , v ) | | λ p - λ δ ( | | u | | p p + | | v | | p p ) - λ C δ ( | | u | | p * p * + | | v | | p * p * ) .

Note that | | u | | p p + | | v | | p p C 1 | | ( u , v ) | | λ p . If δ ≤ (2pλC1)-1, then

I λ ( u , v ) 1 2 p | | ( u , v ) | | λ p - λ C δ ( | | u | | p * p * + | | v | | p * p * ) .

The fact p* > p implies the desired conclusion. □

Lemma 3.8. Under the assumptions of Lemma 3.7, for any finite dimensional subspace

F B, we have

I λ ( u , v ) - as  ( u , v ) F , | | ( u , v ) | | λ .

Proof. By the assumption (H3), it follows that

I λ ( u , v ) 1 p | | ( u , v ) | | λ p - λ a 0 ( | u | α α + | v | β β ) for all  ( u , v ) B .

Since all norms in a finite-dimensional space are equivalent and α, β > p, we prove the result of this Lemma. □

By Lemma 3.6, for λ larger enough and cλ small sufficiently, Iλ satisfies (PS)condition.

Thus, we will find special finite-dimensional subspaces by which we establish sufficiently small minimax levels.

Define the functional

Φ λ ( u , v ) = 1 p N ( | u | p + λ V ( x ) | u | p + | v | p + λ V ( x ) | v | p ) - λ a 0 N ( | u | α + | v | β ) .

It is apparent that Φλ C1(B) and Iλ(u, v) ≤ Φλ (u, v) for all (u, v) ∈ B.

Observe that

inf N | ϕ | p : ϕ C 0 ( N , ) , | ϕ | L α ( N ) = 1 = 0

and

inf N | ψ | p : ψ C 0 ( N , ) , | ψ | L β ( N ) = 1 = 0 .

For any δ> 0, there are φδ, ψ δ C 0 ( N , ) with | ϕ δ | L α ( N ) = | ψ δ | L β ( N ) = 1 and suppφδ, supp ψ δ B r δ ( 0 ) such that | ϕ δ | p p , | ψ δ | p p < δ .

Let w λ ( x ) = ( ϕ δ ( λ p x ) , ψ δ ( λ p x ) ) , then supp w λ B λ - 1 p r δ ( 0 ) . For t ≥ 0, we get

Φ λ ( t w λ ) = t p p w λ λ p - a 0 λ t α N | ϕ δ ( λ p x ) | α - a 0 λ t β N | ψ δ ( λ p x ) | β = λ 1 - N p J λ ( t ϕ δ , t ψ δ ) ,

where

J λ ( u , v ) = 1 p N ( | u | p + | v | p + V ( λ - 1 p x ) ( | u | p + | v | p ) ) - a 0 N ( | u | α + | v | β ) .

We easily prove that

max t 0 J λ ( t ϕ δ , t ψ δ ) α p p α ( α a 0 ) p α p { N ( | ϕ δ | p + V ( λ 1 p x ) | ϕ δ | p } α α p + β p p β ( β a 0 ) p β p { N ( | ψ δ | p + V ( λ 1 p x ) | ψ δ | p } β β p .

Together with V (0) = 0 and | ϕ δ | p p , | ψ δ | p p < δ , this implies that there is Λδ > 0 such that for all λ ≥ Λδ, we have

max t 0 I λ ( t ϕ δ , t ψ δ ) α - p p α ( α a 0 ) p α - p ( 2 δ ) α α - p + β - p p β ( β a 0 ) p β - p ( 2 δ ) β β - p λ 1 - N p . (3.6)

It follows from (3.6) that

Lemma 3.9. Under the assumptions of Lemma 3.7, for any ⊂ > 0, there is Λσ > 0 such that λ ≥ Λσ, there exists w ̄ λ B with w ̄ λ λ > ρ λ , I λ ( w ̄ λ ) 0 and

max t 0 I λ ( t w ̄ λ ) σ λ 1 - N p ,

where ρλ is defined in Lemma 3.7.

Proof. This proof is similar to the one of Lemma 4.3 in [10], it can be easily proved. □

4 Proof of the main result

In the following, we will give the proof of Theorem 2.

Proof. From Lemma 3.9, for any σ > 0 with 0 < σ < α0, there is Λσ > 0 such that for λ ≥ Λσ, we obtain

c λ = inf γ Γ λ max t [ 0 , 1 ] I λ ( γ ( t ) ) σ λ 1 - N p ,

where Γ λ = { γ C ( [ 0 , 1 ] , B ) : γ ( 0 ) = 0 , γ ( 1 ) = w ̄ λ } .

Furthermore, Lemma 3.6 implies that Iλ satisfies (PS)condition. Hence, by the mountain-pass theorem, there is (uλ, vλ) ∈ B satisfying Iλ (uλ, vλ) = cλ and I λ ( u λ , v λ ) = 0 . This shows (uλ, vλ) is a weak solution of (2.1). Similar to the argument in [10], we also get that (uλ, vλ) is a positive least energy solution.

Finally, we prove (uλ, vλ) satisfies the estimate (2.2). Observe that I λ ( u λ , v λ ) σ λ 1 - N p and I λ ( u λ , v λ ) = 0 . we have

I λ ( u λ , v λ ) = I λ ( u λ , v λ ) - 1 θ I λ ' ( u λ , v λ ) ( u λ , v λ ) = 1 p - 1 θ ( u λ , v λ ) λ p + 1 θ - 1 p * λ N K ( x ) ( | u λ | p * + | v λ | p * ) + λ N 1 θ ( u λ H s ( u λ , v λ ) + v λ H t ( u λ , v λ ) ) - H ( u λ , v λ ) 1 p - 1 θ ( u λ , v λ ) λ p .

This shows that (uλ, vλ) satisfies the estimate (2.2). The proof is complete. □

Competing interests

The authors declare that they have no competing interests.

Authors' contributions

The authors contributed equally in this article. They read and approved the final manuscript.

Acknowledgements

The authors would like to appreciate the referees for their precious comments and suggestions about the original manuscript. This research is supported by the National Natural Science Foundation of China (10771212) and the Fundamental Research Funds for the Central Universities (2010LKSX09).

References

  1. Brézis, H, Nirenberg, L: Some variational problems with lack of compactness. Proc Symp Pure Math. 45, 165–201 (1986)

  2. Ambrosetti, A, Rabinowitz, PH: Dual variational methods in critical point theory and applications. J Funct Anal. 14, 349–381 (1973)

  3. Guedda, M, Veron, L: Quasilinear elliptic equations involving critical Sobolev exponents. Non Anal. 12, 879–902 (1989)

  4. Benci, V, Cerami, G: Existence of positive solutions of the equation - Δ u + a ( x ) u = u N + 2 N - 2 in ℝN. J Funct Anal. 88, 90–117 (1990)

  5. Floer, A, Weinstein, A: Nonspreading wave packets for the cubic Schrödinger equation with a bounded potential. J Funct Anal. 69, 397–408 (1986)

  6. Oh, YG: On positive multi-lump bound states of nonlinear Schrödinger equations under multiple well potential. Commun Math Phys. 131, 223–253 (1990)

  7. Clapp, M, Ding, YH: Minimal nodal solutions of a Schrödinger equation with critical nonlinearity and symmetric potential. Diff Integr Equ. 16, 981–992 (2003)

  8. Del Pino, M, Felmer, P: Semi-classical states for nonlinear Schrödinger equations. Annales Inst H Poincaré. 15, 127–149 (1998)

  9. Cingolani, S, Lazzo, M: Multiple positive solutions to nonlinear Schrödinger equation with competing potential functions. J Diff Equ. 160, 118–138 (2000)

  10. Ding, YH, Lin, FH: Solutions of perturbed Schrödinger equations with critical nonlinearity. Calc Var. 30, 231–249 (2007)

  11. Garcia Azoero, J, Peral Alonso, I: Existence and non-uniqueness for the p-Laplacian: Nonlinear eigenvalues. Commun Partial Diff Equ. 12, 1389–1430 (1987)

  12. Alves, CO, Ding, YH: Multiplicity of positive solutions to a p-Laplacian equation involving critical nonlinearity. J Math Anal Appl. 279, 508–521 (2003)

  13. Liu, CG, Zheng, YQ: Existence of nontrivial solutions for p-Laplacian equations in ℝN. J Math Anal Appl. 380, 669–679 (2011)

  14. Mawhin, J, Willem, M: Critical Point Theory and Hamiltonian Systems. Springer-Verlag, New York (1989)

  15. Li, YY, Guo, QQ, Niu, PC: Global compactness results for quasilinear elliptic problems with combined critical Sobolev-Hardy terms. Non Anal. 74, 1445–1464 (2011)

  16. Ghoussoub, N, Yuan, C: Multiple solutions for quasi-linear PDES involving the critical Sobolev and Hardy exponents. Trans Am Math Soc. 352, 5703–5743 (2000)

  17. Brézis, H, Lieb, E: A relation between pointwise convergence of functions and convergence of functional. Proc Am Math Soc. 88, 486–490 (1983)